Marginal adaptation of bulk-fill resin composites with different viscosities in class II restorations: a micro-CT evaluation - İsmail Hakkı Baltacioğlu; Gülbike Demirel; Burcu Öztürk; Fulya Aydin; Kaan Orhan (BMC, 2024)
Abstract Background The purpose of this study is to evaluate the marginal adaptation of bulk-fill resin composites with different viscosities (paste-like and flowable) in Class II restorations using micro-CT imaging. Methods Forty extracted human molars were used. Mesial and distal Class II box cavities (approximately 3 mm x 3 mm x 4 mm) were prepared for each tooth, with cavity floors located 1 mm below the enamel-cementum junction. Following adhesive application, teeth were restored using eight different groups: Group XB: X-tra Base Bulk-fill Flowable (VOCO), Group XF: X-tra Fill Bulk-fill (VOCO), Group FB: Filtek Bulk-fill Posterior (3 M ESPE), Group FF: Filtek Bulk-fill Flowable (3 M ESPE), Group BB: Beautifil-Bulk (SHOFU), Group BF: Beautifil-Bulk Flowable (SHOFU), and Group CO: "as a control group", Clearfil Majesty Posterior (KURARAY) and Group CF: "as a control group", Clearfil Majesty Flow + Clearfil Majesty Posterior (KURARAY). The restored teeth underwent an aging protocol involving 1000 cycles in a water bath fluctuating between 5 ± 1.0 °C and 55 ± 1.0 °C. Post-aging, teeth were immersed in 50% silver nitrate solution for 24 h and then in a film developer solution for 8 h. Microleakage analysis was performed using micro-CT, evaluated with 3D Slicer software. A two-way ANOVA was employed for statistical analysis. Results Two-way ANOVA results indicated significant effects of both viscosity (p < 0.0001) and composite type (p < 0.0001) on marginal adaptation. Viscosity analysis (comparing flowable and paste-like) revealed no significant differences in the FB-FF, XB-XF and BB-BF groups but significant differences in the and CO-CF group, with flowable type exhibiting less microleakage than paste-like type. Conclusions The study suggests that while the viscosity of bulk-fill composites did not significantly affect marginal adaptation, the brand of bulk-fill composite did influence it.